Network analysis reveals aggregation behaviour for an endangered predator at an offshore island. Issue 5 (7th September 2022) - Spector, Michael; Clevenstine, Alyssa J.; Cajandig, Mari; Caldow, Chris; Duncan, Elizabeth A.; Peavey Reeves, Lindsey E.; Freedman, Ryan M.
Abstract: Site fidelity and aggregation behaviour were assessed for giant sea bass Stereolepis gigas (GSB) at Santa Barbara Island, California, USA, from 2018 to 2020. Results indicate seasonal variation in GSB presence, and network analyses revealed a preferred location in a spatially constrained pattern, indicative of aggregation behaviour. Results show GSB aggregated annually during spawning months in the same location, confirming the first known aggregation of GSB at Santa Barbara Island. Identifying and monitoring aggregation sites is vital to ensuring proper protection and ultimate recovery for this protected species in a changing climate.